Manipulating the Rectifying Contact between Ultrafine Ru Nanoclusters and N‐Doped Carbon Nanofibers for High‐Efficiency pH‐Universal Electrocatalytic Hydrogen Evolution. Issue 10 (19th December 2022) - Zhou, Guangyao; Zhang, Sike; Zhu, Yufeng; Li, Jing; Sun, Kang; Pang, Huan; Zhang, Mingyi; Tang, Yawen; Xu, Lin
Abstract: The rational design of ingenious strategies to boost the intrinsic activity and stability of ruthenium (Ru) is of great importance for the substantial progression of water electrolysis technology. Based on Mott–Schottky effect, electronic regulation within a metal/semiconductor hybrid electrocatalyst represents a versatile strategy to boost the electrochemical performance. Herein, a typical Mott–Schottky hydrogen evolution reaction (HER) electrocatalyst composed of uniform ultrafine Ru nanoclusters in situ anchored on N‐doped carbon nanofibers (abbreviated as Ru@N‐CNFs hereafter) through a feasible and scalable "phenolic resin‐bridged" strategy is reported. Both spectroscopy analyses and density functional theory calculations manifest that such rectifying contact can induce the spontaneous electron transfer from Ru to N‐doped carbon nanofibers to generate a built‐in electric field, thus enormously promoting the charge transfer efficiency and HER intrinsic activity. Moreover, the seamless immobilization of Ru nanoclusters on the substrate can prevent the active sites from unfavorable migration, coarsening, and detachment, rendering the excellent structural stability. Consequently, the well‐designed Ru@N‐CNFs afford prominent pH‐universal HER performances with small overpotentials of 16 and 17 mV at 10 mA cm −2 and low Tafel slopes of 31.8 and 28.5 mV dec −1 in acidic and alkaline electrolytes, respectively, which are superior to the state‐of‐the‐art commercial Pt/C and Ru/C benchmarks. Abstract : A Mott–Schottky electrocatalyst composed of uniform ultrafine Ru nanoclusters in situ anchored on N‐doped carbon nanofibers (abbreviated as Ru@N‐CNFs hereafter) is demonstrated. The rectifying contact between Ru nanoclusters and N‐CNFs triggers the electron rearrangement and built‐in electronic field at the heterointerfaces. Benefiting from the Mott–Schottky effect and structural advantages, the Ru@N‐CNFs exhibit superior hydrogen evolution reaction performances over a wide pH range.